COVID-19 và giá cổ phiếu của các ngân hàng thương mại: Nghiên cứu trường hợp Việt Nam - Nguyen Thi My , Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The objective of this study is to analyze the impact of the coronavirus pandemic 2019 (COVID-19) on the stock prices of listed banks in Vietnam. The data sample was collected on a daily basis in Vietnam during the period from January 30, 2020 to January 26, 2021. Accordingly, the data on bank stocks were collected from the transaction results of 15 bank stocks listed on Vietnamese stock market. Unlike previous studies, this study identifies COVID-19 through three different indicators, including the number of domestic COVID-19 cases, the number of imported COVID-19 cases, and the number of deaths due to COVID-9 recorded on a daily basis in Vietnam. The estimated results of the research model show that COVID-19 has a negative impact on the stock prices of banks, and these results are found in three COVID-19 indicators. In particular, the stock prices of banks are impacted most dramatically by the number of COVID-19 deaths and the least dramatically by the number of imported COVID-19 cases, which is an interesting finding of the study. This reveals that the stock prices of banks reacted rather strongly to the development of the COVID-19 pandemic in Vietnam, especially the change in the number of deaths due to COVID-19. In addition, the study also finds the positive impact of market capitalization on the stock prices of banks.